AN ACOUSTIC ANTIFOULING STUDY IN SEA ENVIRONMENT FOR SHIP HULLS USING ULTRASONIC GUIDED WAVES - Habibi, Hossein; Gan, Tat-Hean; Legg, Matthew; Carellan, Ignacio; Kappatos, Vassilios; Tzitzilonis, Vasileios; Selcuk, Cem (International Journal of Engineering Technologies and Management Research, 2016)
Biofouling results in a range of adverse issues for ships and boats such as an increase in hydrodynamic drag force and fuel consumption and increased maintenance cost. To address this issue, toxic antifouling coatings have been developed. However, these toxic coatings can pose threats to marine life. This has led to research on less harmful techniques such as acoustic methods in the main implemented as laboratory trials. In fact, there have been relatively few sea trials and these are poorly documented. The current work has performed one of the few implemented field trials and the only one to be fully documented. In this sea trial, an optimised array of transducers generating ultrasound guided waves was attached to a hull representative plate in a port environment. The results of this work are evidenced by the significant reduction in-situ of a wide range of biofouling materials and organisms. The documented photographical evidence makes up for its scarcity in the published records of antifouling advances using acoustic techniques.